Resilience in liminality: how resilient moves are being negotiated by asylum-seeking families in the liminal context of asylum procedures. (27th May 2020) - Groeninck, Mieke; Meurs, Patrick; Geldof, Dirk; Van Acker, Kaat; Wiewauters, Claire
Abstract: By elaborating on the concept of 'resilient moves', we try to show how resilience in the case of asylum-seeking families living in open, collective reception centres exists in a complicated relationship with vulnerability and is very much a matter of local negotiation rather than mere adaptation in the face of adversity. Building upon consecutive waves of resilience research, this approach inspired by practice theory focuses on the agency of acts performed by families themselves or facilitated by people and structures in various types of relationships to them. It also allows a repoliticization of resilience, explaining how denouncing vulnerability due to structural precarity might constitute resilience through resistance. An in-depth case example of an Afghan family residing for 4 years in a collective reception centre will provide illustrations of our findings and approach.